2013
DOI: 10.1007/s10353-012-0182-8
|View full text |Cite
|
Sign up to set email alerts
|

DG-RAR for the treatment of symptomatic grade III and grade IV haemorrhoids: a 12-month multi-centre, prospective observational study

Abstract: SummaryBackgroundUltrasound-guided techniques represent a new treatment option in the treatment of haemorrhoids. Doppler-guided haemorrhoidal artery ligation (DG-HAL) proved efficacious in early haemorrhoidal disease, but lacks efficacy for stages III/IV. For these patients, haemorrhoidal artery ligation (HAL) has been combined with a running suture to reduce prolapsing haemorrhoidal tissue (recto-anal repair (RAR)).MethodsA prospective observational study was conducted in 184 patients with grade III (58 %) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
1
10
0
4
Order By: Relevance
“…[1][2][3][4][5][6][7] Dearterialization procedures like hemorrhoid artery ligation have a recurrence rate of 5-18% in various studies. [8][9][10][11][12][13][14][15][16][17][18][19] We didn't have long term results in our study but short term results in our study showed that a single treatment can achieve satisfactory results. If the symptoms of bleeding and prolapse due to hemorrhoids are not relieved, further hemorrhoid ligation or other conservative treatment may be tried.…”
Section: Recurrence and Long Term Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7] Dearterialization procedures like hemorrhoid artery ligation have a recurrence rate of 5-18% in various studies. [8][9][10][11][12][13][14][15][16][17][18][19] We didn't have long term results in our study but short term results in our study showed that a single treatment can achieve satisfactory results. If the symptoms of bleeding and prolapse due to hemorrhoids are not relieved, further hemorrhoid ligation or other conservative treatment may be tried.…”
Section: Recurrence and Long Term Resultsmentioning
confidence: 79%
“…It has also been shown to be effective in over 90% of cases, with recurrence of 5-18% in different studies. [8][9][10][11][12][13][14][15][16][17][18][19] In a double blind randomized control trial comparing Doppler guided hemorrhoidal artery ligation and mucopexy with simple ligation of hemorrhoids and mucopexy no advantage was found for the Doppler group.…”
Section: Recurrence and Long Term Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our data, the first consideration concerns the indication. Some papers extend the indication to the use of the THD with mucopexy technique also for IV grade [8,12,18] considering it safe and effective even in those cases. In our experience, the presence of severe pain was present in a statistically significant level in IV grades cases compared to III grades cases (p value 0.00333) and among those cases who had been subjected to a number of mucopexies greater than 4 (p value 0.034).…”
Section: Discussionmentioning
confidence: 99%
“…Значительно увеличить эффективность лечения пациентов при поздних стадиях геморроидальной болезни и снизить частоту рецидива пролапса внутренних узлов удалось А. М. Hussein [28] ДДМ у пациентов с 3 и 4 стадиями геморроя. Рецидив кровотечения возник лишь у 2 % пациентов с 3 стадией заболевания и у 11 % больных с 4 стадией, повторное выпадение внутренних узлов отмечали 8 % оперированных с 3 стадией и 18 % -с 4 стадией геморроя.…”
Section: результатыunclassified